2021
DOI: 10.1155/2021/8537544
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Anti-Nail-Biting Lacquers Containing Shellac and Bitter Herbal Extract

Abstract: The purpose of the present investigation was to formulate and evaluate anti-nail-biting lacquers consisting of bitter herbal extracts. The hydroalcoholic extracts obtained from Andrographis paniculata and Tinospora crispa were determined for phytochemical constituents, total phenolic contents, antioxidant activities, anti-inflammatory activities, and cytotoxicities. Anti-nail-biting lacquers were prepared by using herbal extracts (bittering agent), shellac (film forming polymer), ethanol (volatile solvent), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The anti-inflammatory activity was evaluated by assessing the inhibition of heat-induced denaturation of egg albumin, following a modified version of the procedure outlined by Limmatvapirat et al [ 59 ]. Concisely, the reaction mixture consisted of 0.2 mL of fresh egg albumin, 2.8 mL of phosphate-buffered saline (pH 7.4), and 2 mL of sample solution at concentrations ranging from 0.1 to 4 mg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…The anti-inflammatory activity was evaluated by assessing the inhibition of heat-induced denaturation of egg albumin, following a modified version of the procedure outlined by Limmatvapirat et al [ 59 ]. Concisely, the reaction mixture consisted of 0.2 mL of fresh egg albumin, 2.8 mL of phosphate-buffered saline (pH 7.4), and 2 mL of sample solution at concentrations ranging from 0.1 to 4 mg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…The assessment of a sample's DPPH radical scavenging capacity, reflecting its ability to neutralize DPPH radicals by donating hydrogen atoms or electrons, followed the procedures outlined in our previous studies [61,62]. DPPH radicals, characterized by a deep violet color, display a prominent absorption band at 517 nm.…”
Section: Antioxidant Activity Dpph Radical Scavengingmentioning
confidence: 99%
“…A. paniculata and T. crispa extracts could potentially be used as bittering agents in anti-nail-biting lacquers due to their bitter taste and biological activities. Despite having a substantially higher total phenolic content and antioxidant activity, T. crispa extract was significantly less bitter than A. paniculata extract [ 105 ]. The results demonstrated that bittering compounds and antioxidants could be extracted from both plants using 95% v / v ethanol.…”
Section: Examples Of the Extraction And Chemical Analysis Of Natural ...mentioning
confidence: 99%